624. Microbiota and Associations with Treatment Outcome in Fecal Microbiota Transplantation. (26th November 2018) - Bogdanovich, Tatiana; Morris, Alison; Fitch, Adam; Li, Kelvin; Nettles, Rachel; Sluis-Cremer, Nicolas; Methe, Barbara
Abstract: Background: Fecal microbiota transplantation (FMT) can be an effective treatment of recurrent Clostridium difficile infection (CDI), although non-responsiveness to treatment remains poorly understood. Here we examine the bacterial composition of stool from FMT recipients using culture-independent methods to identify associations between bacterial community structure, route of FMT administration (colonoscopy or freeze-dried encapsulated FMT (capsules)), treatment outcome and donor. We hypothesized that multiple community structures could be associated with and may better define treatment outcome. Methods: We tested this hypothesis by analyzing bacterial composition profiles and their relationship with treatment route, outcome and donor using bioinformatics and multivariate statistics on 16S rRNA gene sequences (16S) from 21 individuals (seven male, 14 female, median 68 years) with recurrent CDI prior to and after FMT. Successful endpoint was defined as no relapse of C. difficile associated diarrhea during 12 weeks post-FMT. There were 17 successes (four colonoscopy, 13 capsules) and four failures (all capsules). Analyses of 16S profiles included permutational analysis of variance (PERMANOVA) and linear regression models applied to bacterial abundances and diversity (as responses). Results: Significant differences were determined between pre- and post-FMT successes and failures ( P < 1e −4, R 2 = 0.24). No differences were seen between route ( P = 0.15) or donor ( P = 0.20). Profiles of failed FMT recipients were more similar to pre-FMT profiles by multidimensional scaling. Analyses of changes in abundance of pre-FMT profiles vs. outcome, controlled for age and sex, identified significant ( P < 0.01) differences across 19 of the 25 most abundant taxa. Of the five most abundant taxa, Enterobacteriaceae and Esherichia-Shigella decreased significantly in successful outcomes, while Faecalibacterium, Blautia, and Bacteroides increased. However, variation in individual composition was also significant suggesting that multiple profiles represent successful outcomes. Conclusion: Increases in microbiota diversity are generally achieved in successful FMT regardless of administration route, although more than one bacterial composition profile can be identified. Disclosures: All authors: No reported disclosures.